2020
DOI: 10.1016/j.annemergmed.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

High-Flow Nasal Cannula Versus Conventional Oxygen Therapy in Relieving Dyspnea in Emergency Palliative Patients With Do-Not-Intubate Status: A Randomized Crossover Study

Abstract: Study objective: Palliative patients often visit the emergency department (ED) with respiratory distress during their end-of-life period. The goal of management is alleviating dyspnea and providing comfort. High-flow nasal cannula may be an alternative oxygen-delivering method for palliative patients with do-not-intubate status. We therefore aim to compare the efficacy of high-flow nasal cannula with conventional oxygen therapy in improving dyspnea of palliative patients with do-not-intubate status who have hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 28 publications
2
41
1
1
Order By: Relevance
“…Full-text review of 38 potentially eligible studies identified 20 eligible studies. Of these, 17 were systematic reviews (SRs) 15,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and three were RCTs [41][42][43] (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Full-text review of 38 potentially eligible studies identified 20 eligible studies. Of these, 17 were systematic reviews (SRs) 15,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and three were RCTs [41][42][43] (Fig. 1).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Therefore, 12 RCTs with 1,989 patients were included in analyses, including nine RCTs from the original review and three RCTs from the updated search. [41][42][43][44][45][46][47][48][49][50][51][52] No trial directly evaluated HFNC in patients with COVID-19 or other coronavirus infections. Table 1 summarizes study characteristics.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to NIV for undifferentiated respiratory failure, there was no difference between NHF for any outcome in a single RCT [20]. In contrast, a small RCT in palliative patients with limitations on invasive ventilation found dyspnea was reduced with NHF compared to NIV [77]. NHF may have a role in some ED patients who would not be offered intubation or when NIV is not well tolerated.…”
Section: Nhf In the Ed And Palliative Carementioning
confidence: 92%